2021
DOI: 10.1038/s41420-021-00407-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding the role of lncRNA in programmed cell death

Abstract: Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides but not translated into proteins. LncRNAs regulate gene expressions at multiple levels, such as chromatin, transcription, and post-transcription. Further, lncRNAs participate in various biological processes such as cell differentiation, cell cycle regulation, and maintenance of stem cell pluripotency. We have previously reported that lncRNAs are closely related to programmed cell death (PCD), which includes apoptosis, autophagy, necropt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 93 publications
0
98
0
1
Order By: Relevance
“…Moreover, various types of RCD mechanisms have recently been identified along with conventional RCD mechanisms, such as apoptosis [ 174 ]. Moreover, RCDs can play an important role in skin.…”
Section: Signals and Signaling Pathways In Hfscsmentioning
confidence: 99%
“…Moreover, various types of RCD mechanisms have recently been identified along with conventional RCD mechanisms, such as apoptosis [ 174 ]. Moreover, RCDs can play an important role in skin.…”
Section: Signals and Signaling Pathways In Hfscsmentioning
confidence: 99%
“…Several lines of evidence have shown that lncRNAs are capable of influencing different cellular functions that are critical to tumorigenesis, such as cell proliferation, differentiation, migration, immune response, and apoptosis [41][42][43][44][45][46][47]. Furthermore, lncRNAs have been found to act as tumor suppressors or oncogenes [48][49][50][51], and, of note, a number of lncRNAs have been reported to be significantly deregulated in tumors [52][53][54][55].…”
Section: Long Non-coding Rna Structures and Functionsmentioning
confidence: 99%
“…lncRNAs play an important role in many life activities, such as epigenetic regulation, cell cycle regulation, and regulation of cell differentiation [ 10 ]. In particular, the abnormal function or expression of lncRNA may be closely related to various biological processes, including ferroptosis [ 11 ]. For example, the lncRNA LINC00336 inhibits ferroptosis in lung cancer by functioning as a competitive endogenous RNA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%